Modifying effects of menthol against benzo(a)pyrene-induced forestomach carcinogenesis in female Swiss mice - Santo, Sara Gomes Espírito [UNESP]; Romualdo, Guilherme Ribeiro [UNESP]; Santos, Leandro Alves dos [UNESP]; Grassi, Tony Fernando [UNESP]; Barbisan, Luís Fernando [UNESP] (Wiley, 2021)
Benzo(a)pyrene (BaP) is a polycyclic aromatic hydrocarbon widespread in the environment and closely associated to tobacco use, which is an important risk factor for highly incident stomach cancer. Menthol, a monoterpene extracted from Mentha genus species, has multiple biological properties, including anti-inflammatory and gastroprotective properties, but its effects on carcinogenesis are still to be fully understood. Thus, we evaluated the modifying effects of Ment against BaP-induced forestomach carcinogenesis. Female Swiss mice received BaP by intragastrical (i.g.) administration (50 mg/kg of body weight [b wt], 2×/week), from weeks 1–5 weeks. Concomitantly, mice received Menthol at 25 (Ment25) or 50 (Ment50) mg/kg b wt (i.g, 3×/week). Animals were euthanized at weeks 5 (n = 5 mice/group) or 30 (n = 10 mice/group). At week 5, both Ment doses reduced peripheral leukocyte blood genotoxicity 4 h after the last BaP administration, but only Ment50 attenuated this biomarker 8 h after the last BaP administration. In accordance to these findings, both Ment interventions attenuated BaP-induced increase in the percentage of H2A.X-positive forestomach epithelial cells. Moreover, Ment50 reduced cell proliferation and apoptosis (i.e., Ki-67 and caspase-3, respectively) in forestomach epithelium but exerted no significant effects on NFκB, and Nrf2 protein levels. At week 30, Ment50 reduced by ~55% the incidence of BaP-induced forestomach diffuse hyperplasia and multiplicity of forestomach tumors (squamous cell papillomas and carcinomas). Our findings indicate that Ment50, administered during initiation phase, attenuates forestomach carcinogenesis by reducing early genotoxicity, cell proliferation, and apoptosis induced by BaP.
Keywords: benzo(a)pyrene; female Swiss mice; forestomach carcinogenesis; genotoxicity; menthol